2020
DOI: 10.1177/2053369120957514
|View full text |Cite
|
Sign up to set email alerts
|

The British Menopause Society & Women’s Health Concern 2020 recommendations on hormone replacement therapy in menopausal women

Abstract: • All women should be able to access advice on how they can optimise their menopause transition and the years beyond.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
143
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(147 citation statements)
references
References 171 publications
(20 reference statements)
0
143
0
4
Order By: Relevance
“…Current guidelines recommend that MHT should be tailored to each woman, using the lowest effective dose of estrogen and progestogen to achieve an optimal balance between efficacy and safety with respect to breast cancer and cardiovascular effects, while addressing patient-specific needs and other risk factors [13,14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Current guidelines recommend that MHT should be tailored to each woman, using the lowest effective dose of estrogen and progestogen to achieve an optimal balance between efficacy and safety with respect to breast cancer and cardiovascular effects, while addressing patient-specific needs and other risk factors [13,14].…”
Section: Discussionmentioning
confidence: 99%
“…Menopausal hormone therapy (MHT) is highly effective in reducing the vasomotor symptoms of menopause; a metaanalysis of 47 studies that included more than 8300 menopausal women reported that, of 16 treatments, MHT was the most effective for vasomotor symptoms [12]. The International Menopause Society and British Menopause Society guidelines on hormone therapy in menopause both recommend that MHT is the most effective treatment for reducing the vasomotor symptoms of menopause and should be tailored to each woman, using the lowest effective dose [13,14]. This is also reflected in the Chinese guideline on menopause management and hormone therapy, which recommends MHT for the treatment of vasomotor symptoms within 10 years following menopause [15].…”
Section: Introductionmentioning
confidence: 99%
“…Persistent unscheduled bleeding on HRT beyond six months warrants investigation with ultrasound scan and endometrial biopsy if clinically indicated. 11 Counselling patients who take seq- or con-HRT about unscheduled bleeding in the initial six months is crucial. Women need to be informed to report unscheduled vaginal bleeding at the three-month review appointment or promptly if it occurs after the first three months.…”
Section: Discussionmentioning
confidence: 99%
“…Hormonal replacement therapy (HRT). HRT is usually prescribed to reduce the vasomotor symptoms associated with the menopausal transition [ 100 , 101 ]. However, population-based studies suggest that HRT worsens migraine [ 32 , 102 , 103 ].…”
Section: Considerations On the Treatment Of Perimenopausal Migrainementioning
confidence: 99%